International Chamber of Commerce Arbitration / Second Edition - Craig W. Laurence; Park William W; Paulsson Jan (Oceana Publications, 1990)
Preface, Abbreviations, The Institution, General Characteristics, The Organizational Framework, Costs, Types of Arbitration Agreements, The Validity of the Arbitration Agreement, Indispensable Elements, Generally Recommended Additional, Occasionally Useful Elements, Pathological Elements, ICC Arbitration in Practice, Bringing Arbitration Under the Rules, Arbitral Jurisdiction, Constituting the Arbitral Tribunal and Determing the Place of Arbitration, Arbitrator Disqualification or Incapability, Advance to Cover Costs, Terms of Reference, Rules Governing the Proceedings, Choice of Sustantive Law, Amiable Composition, Arbitral Awards, Hearings and Proof and Ancillary Proceedings, The Impact of National Law, Trends in International Commercial Arbitration, Appendices, Index.